(untitled) (Sains Humanika, 2018)
The purpose of this study is to get an expert agreement on the elements of Green Skills that need to be incorporated into the curriculum of the designated subjects as well as to create the individual who will be the workforce in the care of the environment. The objective of this study is to obtain expert opinion and consensus on Green Skills elements. This is a quantitative study using the questionnaire given to the expert. All data collected were analyzed using Fuzzy Delphi Method. The findings showed that all elements of Green Skills are in line with the conditions, the threshold value is less than 0.2, the group of experts is over 75% and the Fuzzy Score exceeds 0.5. This suggests that the Green Skills element is indispensable among students based on expert agreements.